ICT use and preference among hypertensive patients during COVID -19 pandemic in Selangor: a cross-sectional study / Mohd Ramadan Ab Hamidand Nurul Shafiqah Abdul Rahim - Ab Hamid, Mohd Ramadan; Abdul Rahim, Nurul Shafiqah (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
Patients with hypertension acquire health information from healthcare practitioners or online sources. During the pandemic, patients are likely to search for health-related information primarily through information and communication technologies (ICTs). This paper aims to assess the use and preference of ICTs among hypertensive patients. We conducted a cross-sectional online survey-based study from April to October 2020 involving 96 patients with hypertension. The questionnaire collected information regarding demographics, patients' preference for ICTs platforms, quality of online information and belief towards the use of ICTs. A Pearson chi-square test for association and adjusted regression analysis were performed. Among all patients who participated, 99% reporting owning smartphone, with an active internet connection. The most used ICT for obtaining information about hypertension was web browsers, followed by YouTube and Facebook. Social media use was significantly associated with education level and residential area. The outcome of the regression analysis indicated that males were 1.31 times more likely to use social media platforms than females. Finally, females were three times more likely to associate internet-based health education with better blood pressure control. Understanding how people with hypertension utilise and prefer ICTs may aid in improving their outcomes through the possible uses and benefits of ICTs. By determining the most frequently used ICT platform, health practitioners can devote more attention to it.